2013
DOI: 10.1007/s12161-013-9679-4
|View full text |Cite
|
Sign up to set email alerts
|

Aroma, Sugar and Anthocyanin Profile of Fruit and Seed of Mahlab (Prunus mahaleb L.): Optimization of Bioactive Compounds Extraction by Simplex Lattice Mixture Design

Abstract: Türkiye' de yaygın biçimde tarımı yapılan mahlep bitkisi boya, kozmetik, fırıncılık endüstrisinde kullanılmasının yanısıra halk arasında ilaç olarak da kullanılmaktadır. Bu çalışmada, ekonomik değeri olan ihracat potansiyeli oldukça yüksek olan beyaz mahlebin (Prunus mahaleb L.) bazı karakteristik özellikleri ile çekirdek yağının yağ asitleri kompozisyonu incelenmiştir. Buna göre çekirdeklerin yağ içerikleri %16.11±0.12, protein içerikleri %31.9297±0.437 ve 100 tane ağırlığı ise 3.835±0.016 g olarak bulunmuştu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…This might be due to the similar specific anthocyanin profiles of grape varieties. E a values of anthocyanin degradation for different fruits were reported as 52.39 to 54.50 kJ/mol for pomegranate arils (Karaaslan et al, 2013), 58.95 kJ/mol for blackberry (Wang and Xu, 2007), and 45.47 kJ/mol for mahlap fruit (Ozturk et al, 2014). Lower E a values indicate a higher stability of anthocyanin against temperature increase.…”
Section: Thermal Degradation Kinetics Of Grapes Anthocyaninmentioning
confidence: 99%
“…This might be due to the similar specific anthocyanin profiles of grape varieties. E a values of anthocyanin degradation for different fruits were reported as 52.39 to 54.50 kJ/mol for pomegranate arils (Karaaslan et al, 2013), 58.95 kJ/mol for blackberry (Wang and Xu, 2007), and 45.47 kJ/mol for mahlap fruit (Ozturk et al, 2014). Lower E a values indicate a higher stability of anthocyanin against temperature increase.…”
Section: Thermal Degradation Kinetics Of Grapes Anthocyaninmentioning
confidence: 99%
“…Identification and peak assignment of anthocyanins in mfce was based on comparison of their retention times and UV-Vis spectra with those of standards and on published data on P. mahaleb L. fruit anthocyanin characterization by MS analysis [12][13][14]. Figure 1A shows the HPLC anthocyanin profile of mfce.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…5A). Ozturk et al [13] found that the major sugars in P. mahaleb fruits were glucose, fructose and sucrose. Our results are in agreement with several studies reporting that sweetness in cherry fruits is mainly due to glucose and fructose, followed by sorbitol, while sucrose was identified in very low amounts [38,40,[56][57][58].…”
Section: Sugars Organic Acids and Ascorbic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, 12 different terebinth fruits were analyzed. In order to yield the highest amount of phenolic compound, a simplex lattice mixture design was used to determine the best solvent composition as it is well known that solvent type significantly affects extracted phenolic compound quantity (Al-Farsi and Lee, 2008;Karaman et al, 2013;Ozturk et al, 2014). In summary, our study aimed to determine: 1) the optimum solvent mixture of acetone, methanol, and water, based on maximization of phenolic contents, 2) the bioactive properties (total phenolic content and antiradical activity), 3) the antimicrobial characteristics, and 4) the fatty acid compositions of the extracts of 12 different Pistacia terebinthus fruits, cultivated in different regions of Turkey.…”
Section: Introductionmentioning
confidence: 99%